Combined influence of leisure‐time physical activity and hip circumference on all‐cause mortality12. (12th March 2013) - Østergaard, J.N.; Grønbæk, M.; Ängquist, L.; Schnohr, P.; Sørensen, T.I.A.; Heitmann, B.L.
Abstract Hip circumference has been shown to be inversely associated with mortality. Muscle atrophy in the gluteofemoral region may be a possible explanation and thus physical activity is likely to play an important role. Objective: To estimate the combined effects of hip circumference and physical activity on mortality. Design and Methods: From the Copenhagen City Heart Study, 3, 358 men and 4, 350 women aged 21 to 93 years without pre‐existing diagnosis of diabetes, stroke, ischemic heart disease, or cancer in 1991‐1994 and with complete information on the variables of interest were included in the analyses. The participants were followed to 2009 in the Danish Civil Registration System, with 1.3% loss to follow‐up and 2, 513 deaths. Hazard ratios (HR) were estimated for combinations of physical activity and hip circumference. Results: Hip circumference was inversely associated with mortality irrespective of being physically active or not. However, being physically active seemed to counterbalance some of the adverse health effects of a small hip circumference; when comparing inactive to active, the excess mortality at the 25th percentile of hip circumference is 40% in men (HR = 1.40, 95% CI: 1.14‐1.72) and 33% in women (HR = 1.33, CI: 1.10‐1.62). These associations were observed after adjustment for waist circumference and weight change in the 6 months before the examination. Conclusion: Less effects of physical activity were found in individuals with greater hip circumferences. A small hip circumference appears hazardous to survival. However, being physically active may counterbalance some of the hazardous effects of a small hip circumference.